Cloning, characterization, in vitro and in planta expression of a necrosis-inducing Phytophthora protein 1 gene npp1 from Phytophthora cinnamomi - Martins, Ivone M. (2019)
The soil-borne oomycete Phytophthora cinnamomi is a highly destructive Phytophthora species associated with the decline of forest. This pathogen secretes a novel class of necrosis-inducing proteins known as Nep1-like proteins (NLPs). In this work, we report the sequencing and molecular characterization of one of these proteins, more specifically the necrosis-inducing Phytophthora protein 1 (NPP1). The ORF of the npp1 gene (EMBL database AM403130) has 768 bp encoding a putative peptide of 256 amino acids with a molecular weight of approximately 25 kD. In order to understand its function, in vitro gene expression was studied during growth in different carbon sources (glucose, cellulose, and sawdust), and at different times of infection, in vivo by RT-qPCR. The highest expression of the npp1 gene occurred in glucose medium followed by sawdust. In vivo infection of Castanea sativa roots with P. cinnamomi revealed a decrease in npp1 expression from 12 to 24 h; at 36 h its expression increased suggesting the existence of a complex mechanism of defense/attack interaction between the pathogen and the host. Expression of recombinant npp1 gene was achieved in Pichia pastoris and assessed by SDS-PAGE analysis of the protein secreted into the culture supernatant, revealing the presence of the NPP1 protein.